BRIEF COMMUNICATION ON PARENTS’ SATISFACTION LEVEL AND SAFETY PERCEPTION ON PUBLIC CLIMBING EQUIPMENT IN MALAYSIA: A PRELIMINARY STUDY - Cheah Kah Ling; Raja Ahmad Azmeer; Mohd Shahrizal Dolah; Saiful Hasley; Jusang Bolong (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Children injury caused by unsafe climbing equipment is a public concern topical issue. This study aimed to measure the satisfaction level and safety perception of parents on public climbing equipment in Malaysia. An online survey was conducted with 50 Malaysian residents who aged between 18 years old to 45 years old. Collected data was analysed descriptively using SPSS version 21.0. The findings showed the satisfaction level of parents towards the existing public climbing equipment were relatively low (90%). It reflected the low confidence level of parents towards the safety level of public climbing equipment which may lead them to reduce the usage of the equipment. 92% of parents agreed that by improving the design in terms of height, materials and protective shade can help to improve the safety level of public climbing equipment which will reduce falls injury. The result revealed that the safety level of existing public climbing equipment was extremely low and thus, parents have low confidence on the safety level of existing public climbing equipment. In this regard, this study can be further extended by investigating the unsafe features and generate a new guideline or design framework of public climbing equipment which will provide crucial information for equipment designer, developer, safety inspector and local authorities to fulfil their roles and responsibilities.